Early-opening-to-traffic asphalt pavement for airfield rehabilitation - Rahman, Taqia (2021)
A large number of scheduled flights at major civil airports has made it necessary that runway repair and overlay be carried out without interfering with flight schedules. Asphalt overlaying at night has become one practical solution to this issue. Using this method, the runway is closed at night for several hours and immediately opened to aircraft traffic in the morning. Generally, at the end of the time window, several hours are needed for the pavement to cool down before re-opening. For a busy airport, the cooling is an otherwise undesirable use of time. Shortening the asphalt cooling time would allow airport authorities to quickly open the new pavement to traffic and thus reduce airport closures. It would also allow contractors to place the maximum amount of HMA each night, increasing the target length to be paved, thus shortening the overall project contract and increasing construction efficiency. This thesis investigates strategies for reducing the cooling time of asphalt overlays to accelerate airport pavement construction while still delivering satisfactorily constructed pavements during airfield pavement repair/rehabilitation. Three strategies were reviewed: (1) Defining and selecting the warmest hot-mix-asphalt (HMA) temperature at opening to traffic commensurate with adequate performance and safe operations, (2) Reducing the cooling time by using warm-mix-asphalt (WMA), (3) Decreasing the pavement temperature by spraying cool water onto the new asphalt. To investigate the first and second strategies, laboratory evaluation of rutting performance and interface shear strength at high temperature and high loads was performed to investigate the allowable asphalt temperature for trafficking of HMA and WMA airfield pavements. Bituminous mixtures with unmodified bitumen (40/60 pen. grade), SBS polymer modified binder, and both binders containing WMA additives (wax and chemical) were manufactured and tested to examine the bitumen effect on the pavement performance at different opening temperatures. The rutting performance and interface shear bond strength of the bituminous mixtures at traffic opening temperatures were then predicted using a simple linear viscous approach and the Mohr-Coulomb failure model, respectively. Moreover, to simulate the effect of each strategy on airport closure time and pavement construction period, a one-dimensional (1D) heat-transfer model, using a finite element (FE) program (ABAQUS) was developed. To investigate the third strategy, small-scale 11-cm-thick asphalt slabs were constructed inside steel moulds to measure cooling rates due to both natural cooling and water spray cooling, using embedded thermocouples and an infrared thermometer. Various temperatures and flow rates of water spraying were considered. A three-dimensional (3D) heat transfer analysis of the laboratory-scale FE model was then used to determine the heat transfer coefficients of the water cooling by trial-and-error matching of temperature in the 3D model to the temperatures from the thermocouple readings. In addition, cores were taken from the asphalt slabs for Cantabro and indirect tensile strength (IDT) testing so as to investigate the possible drawbacks of water cooling of newly laid asphalt in terms of the long-term durability and moisture susceptibility. Regarding the first strategy, the results indicate that at the traffic-opening temperature of 60°C, as set by many agencies and specifications, the newly laid asphalt has gained sufficient strength to resist permanent deformation and interface failure caused by aircraft load and braking. The results, however, suggested that different mixtures and tack coat materials, particularly those containing polymer-modified bitumen (PMB), could be re-opened to air traffic at a considerably higher temperature (up to 80°C). This result encourages airport authorities and agencies to be more adaptive with the traffic-opening temperature specification, particularly for asphalt with PMBs. The cooling analysis showed that for the cases studied, raising the critical trafficking temperature could reduce the closure of an airport during night-time construction by 17-114 minutes (26-63% reductions) depending on the asphalt mixture type, environmental condition (wind speed) and traffic-opening temperature. For the second strategy, the laboratory tests indicate that, in general, the WMAs have a rutting performance at high temperatures during the opening to traffic similar to, or better than HMA. It was found that, compared to HMA, a WMA having a wax additive showed excellent rutting resistance, enabling the pavement to be opened to traffic at a higher temperature. This is likely because, at in-service temperatures, the wax additives solidify (crystallize) and thus improve stiffness and rutting resistance of the mixture. Moreover, the cooling analysis showed that, in comparison to HMA, the use of this WMA could shorten the closure time of airport during the night-time construction by 8–67 min (5–73% reductions compared to HMA cooling time) depending on the asphalt overlay thickness, specified traffic opening temperature and WMA production temperature.